2020
DOI: 10.1186/s12891-020-3124-9
|View full text |Cite
|
Sign up to set email alerts
|

Posterior-only surgical correction with heavy halo-femoral traction for the treatment of rigid congenital scoliosis associated with split cord malformation

Abstract: Background: Whether or not, prophylactic neurosurgical interventions of split cord malformation (SCM) before undertaking corrective surgery was the focus of debate. The present study was performed to evaluate the safety and efficacy of posterior-only surgical correction with heavy halo-femoral traction for the treatment of rigid congenital scoliosis (RCS) associated with SCM. Methods: From 2011 to 2017, 24 patients suffered from RCS associated with SCM underwent posterior-only surgical correction with heavy ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Sponseller et al [14] found that HGT did not increase the main coronal curve or sagittal plane correction in a multicenter, retrospective, nonrandomized comparison study. Compared to HGT, which has a limited traction weight, HFT can offer stronger and simultaneous traction forces [15,16]. In our study, the mean preoperative major curve was 97.99°± 11.47°, with a mean flexibility of 15.68% ± 6.65%, and it had only a 6.23% ± 1.79% improvement on the fulcrum film; however, after a mean 18.15 ± 2.01 kg (46.46% ± 5.36% of body weight) maximum traction weight for 18.26 ± 2.43 days, the average correction rate added 17.83% ± 5.41%, reaching a total of 39.74% ± 6.22% at the end of HFT.…”
Section: Discussionmentioning
confidence: 99%
“…Sponseller et al [14] found that HGT did not increase the main coronal curve or sagittal plane correction in a multicenter, retrospective, nonrandomized comparison study. Compared to HGT, which has a limited traction weight, HFT can offer stronger and simultaneous traction forces [15,16]. In our study, the mean preoperative major curve was 97.99°± 11.47°, with a mean flexibility of 15.68% ± 6.65%, and it had only a 6.23% ± 1.79% improvement on the fulcrum film; however, after a mean 18.15 ± 2.01 kg (46.46% ± 5.36% of body weight) maximum traction weight for 18.26 ± 2.43 days, the average correction rate added 17.83% ± 5.41%, reaching a total of 39.74% ± 6.22% at the end of HFT.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional supplement treatments were performed during the traction to increase body weight and improve nutritional status. Respiratory training, such as deep respiration and balloon exercise, was applied [ 12 , 13 ] .…”
Section: Methodsmentioning
confidence: 99%
“…Compared to HGT, which has a limited traction weight, HFT can offer stronger and simultaneous traction forces. [15,16] In our study, the mean preoperative major curve was 97.99°±11.47°, with a mean exibility of 15.68% ±6.65%, and it had only a 6.23%±1.79% improvement on the fulcrum lm; however, after a mean 18.15±2.01-kg (46.46%±5.36% of body weight) maximum traction weight for 18.26±2.43 days, the average correction rate added 17.83%±5.41%, reaching a total of 39.74%±6.22% at the end of HFT. Similarly, Wang [7] reported 21 cases with extremely severe rigid scoliosis treated by HFT before posterior vertebral column resection.…”
Section: Complicationsmentioning
confidence: 99%